Mechanisms and safety evaluation of stir-fried atractylodis macrocephalae rhizoma with aurantii fructus in the treatment of inflammatory bowel disease: a study based on organ-on-a-chip model - Zhang, Weidong; Liu, Chanming; Chen, Wei; Zhu, Yueqin; Gu, Zhengrong; Xue, Ping; Zhuang, Xin; Wei, Yuan; Ye, Jiexian; Xu, Xi; Zhang, Jing; Chen, Zaozao; et al. (Frontiers in Pharmacology, 2026)
BackgroundStir-fried atractylodis macrocephalae rhizoma (AMR) with aurantii fructus (AF) (SFALCA), a classical prescription of traditional Chinese medicine (TCM), has been widely used for promoting gastrointestinal health for centuries, with multiple pharmacological properties such as anti-tumor, anti-inflammatory, anti-aging, antioxidant, and antibacterial effects. Inflammatory bowel disease (IBD) is an immune-mediated chronic gastrointestinal inflammatory disorder that causes long-term distress to patients. Despite its widespread use, the specific effects of SFALCA on intestinal barrier function and underlying mechanisms remain unclear. Furthermore, interspecies discrepancies in animal studies and the physiological constraints of existing in vitro models synergistically limit the translational potential of current findings on this botanical combination.MethodsTo investigate the active components, mechanisms of SFALCA in treating IBD and assesses its safety. We designed an innovative organ-on-a-chip system to simulate the human intestinal and liver environment. By stimulating with LPS/PMA, we established an in vitro IBD model and intervened with SFALCA and its extracts. Immunofluorescence staining was used to evaluate the success of the model. TEER measurements were employed to assess the integrity of tight junctions. Alcian Blue staining characterizes the expression of acidic mucins in HT-29 cells. The levels of inflammatory cytokines and the human albumin were measured using ELISA kits. The cytotoxicity of TCM to liver was evaluated by CellTiter-Glo® 3D test according to the manufacturer’s instructions. Flow cytometric analysis was used to detect the polarization of macrophages in intestinal inflammation model after drug treatment. RNA-seq analysis was used to identify key targets and pathways.ResultsThe results showed that SFALCA and its extracts significantly increased transepithelial electrical resistance (TEER) and Zonula occludens-1 (ZO-1) expression, while inhibiting LPS/PMA-induced IL-6 levels and the proportion of M1 macrophages. Further analysis revealed that the main active components of SFALCA, Atractylenolide I and Naringin, exert anti-inflammatory effects by inhibiting the Interleukin-17C (IL-17C) mediated positive feedback loop. Additionally, organ-on-a-chip technology confirmed that SFALCA showed no significant toxicity to the liver.ConclusionIn conclusion, this study elucidates the active components and mechanisms of SFALCA in treating IBD and assesses its safety, providing a reliable in vitro platform for future therapeutic strategies.